A coating composed of chitosan and Cymbopogon citratus (Dc. Ex Nees) essential oil to control Rhizopus soft rot and quality in tomato fruit stored at room temperature. Issue 6 (1st November 2016) - Athayde, A.J.A.A.; de Oliveira, P.D.L.; Guerra, I.C.D.; da Conceição, M.L.; de Lima, M.A.B.; Arcanjo, N.M.O; Madruga, M.S.; Berger, L.R.R.; de Souza, E.L.
ABSTRACT: This study evaluated the efficacy of the combined application of chitosan (CHI) and Cymbopogon citratus (Dc. Ex Nees) (lemongrass) essential oil (CCEO) to control Rhizopus stolonifer in fresh tomato ( Lycopersicon esculentum Mill.) fruit at room temperature (25°C) storage. The effects of the treatment (CHI and CCEO) on some quality characteristics of the fruit, namely weight loss, firmness, soluble solids, titratable acidity, pH, ascorbic acid, color, and sensory acceptability were also assessed. The minimum inhibitory concentrations of CHI and CCEO against R. stolonifer were 8 mg/mL and 5 µL/mL, respectively. Subinhibitory concentrations of CHI and CCEO (CHI 4 mg/mL, CCEO 1.25 µL/mL), alone and in combination, inhibited fungal spore germination and damaged spore membrane integrity. The CHI-CCEO coating decreased the severity of Rhizopus soft rot in tomato fruit; however, the coating more strongly delayed the infection when the fruit were artificially contaminated after coating application. The application of the coating preserved the general quality of tomato fruit as measured using a variety of physicochemical and sensory attributes. These results indicate that coatings composed of CHI and CCEO could represent promising postharvest treatments to inhibit Rhizopus soft rot in tomato fruit.